2019
DOI: 10.3390/en12224327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Oxide (III)–Therminol 66 Nanofluid as a Novel Working Fluid in a Convective Radiator Heating System for Buildings

Abstract: This work investigates the use of iron oxide (III)–therminol 66 oil-based nanosuspensions in a convective heating system with potential heating applications in the buildings sector. In an experimental study, characteristics of nanofluids were measured, including heat capacity, thermal conductivity, and density. The influences of mass flow rate and concentration of nanofluid on various parameters were quantified, such as pressure loss, friction coefficient, and heat transfer rate. For a concentration of 0.3 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…These improvements are higher than those found in the literature for spinal and magnetic material in thermal oils, which is always lower than 30%, being Fe 3 O 4 the typical magnetic nanomaterial used. 23,43,44 A similar increase in thermal conductivity for nanofluids based on magnetic NPs was found by Hussain et al using Fe 3 O 4 , but in that case, these NPs were used for decorating the surface of MWCNTs. 45 The highest increase is found for the nanofluid with the highest volume fraction value.…”
Section: Nanofluids Performancesupporting
confidence: 64%
“…These improvements are higher than those found in the literature for spinal and magnetic material in thermal oils, which is always lower than 30%, being Fe 3 O 4 the typical magnetic nanomaterial used. 23,43,44 A similar increase in thermal conductivity for nanofluids based on magnetic NPs was found by Hussain et al using Fe 3 O 4 , but in that case, these NPs were used for decorating the surface of MWCNTs. 45 The highest increase is found for the nanofluid with the highest volume fraction value.…”
Section: Nanofluids Performancesupporting
confidence: 64%
“…Sarafraz et al [21] investigated the characteristics of iron oxide (III)-Therminol 66 oil based nanofluid in a convective radiator heating system. The experimental setup consisted of a convective radiator, a loop section, and the measurement tools.…”
Section: Experimental Measurements and Setups For Natural And Forced Convection Under The Laminar Regimementioning
confidence: 99%
“…Starting from these experimental campaigns, it has already been observed how the presence of nanofluids significantly affects the thermal efficiency compared to that of traditional fluids. Several experimental campaigns showed that nanofluids could be used efficiently in solar systems applications [17,49], in heating and cooling systems for buildings [21], automobiles [14,42], and in electronics [11,18,31]. The intent of this study is to provide an overview of the results and progress achieved using nanofluids in various experimental systems under turbulent and laminar regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hussein et al presented a maximum ~9.9% rise in pressure drop using MWCNT/water nanofluids which varied substantially with concentration (0.075–0.25 mass%) [ 12 ]. Sarafraz et al showed a ~37.5% rise in pressure drop due to friction and viscosity enhancement (with concentration) for iron oxide-based therminol nanofluids [ 13 ]. Thermodynamically, flow resistance due to viscosity enhancement causes viscous dissipation, which increases the entropy generation of a thermal system.…”
Section: Introductionmentioning
confidence: 99%